Relationship between psychopathological symptoms and quality of life in women and men - Ruiz Martinez, Ana Olivia (2018)
Mental health problems, which affect biopsychosocial development of people, worsen because people take too long to come to health services. This situation shows the need for early detection of these problems in open populations. Considering this, the present research aimed to assess the relationship between psychopathological symptoms and quality of life in women and men. The study population consisted of 465 inhabitants of the State of Mexico, who answered the SCL-90-R and WHOQOL- BREF questionnaires. Results: women have higher scores of psychopathological symptoms and lower quality of life than men. Mental health problems affect quality of life in different ways according to gender: in women, depression and global symptoms stand out; and in men, somatization, global symptoms and depression are the most common ones. This paper discusses the need for prevention and early detection of incipient symptoms of mental health problems through community work.